2017
DOI: 10.1007/s00421-017-3676-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training programs based on ipsilateral voluntary and stimulated contractions on muscle strength and monopedal postural control of the contralateral limb

Abstract: The purposed training program with NMES vs VOL contractions induced strength gains but did not permit any improvement of contralateral monopedal postural control in healthy young subjects. This has potential for therapeutic application and allows clinicians to focus their training programs on dynamic and poly-articular exercises to improve the postural control in young subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…As noted in preceding sections, bilateral alterations in the state of brain circuits that constitute the classical motor network in both hemispheres are frequently observed following unilateral NMES. It is therefore particularly salient that these NMES variants can increase the force-generating capacity of homologous muscles in the limb opposite to the one in receipt of stimulation (Cabric and Appell, 1987;Hortobágyi et al 1999;Zhou et al 2002;Huang et al 2007;Kadri et al 2017).…”
Section: Brain Circuitry Engaged By Nmesmentioning
confidence: 99%
“…As noted in preceding sections, bilateral alterations in the state of brain circuits that constitute the classical motor network in both hemispheres are frequently observed following unilateral NMES. It is therefore particularly salient that these NMES variants can increase the force-generating capacity of homologous muscles in the limb opposite to the one in receipt of stimulation (Cabric and Appell, 1987;Hortobágyi et al 1999;Zhou et al 2002;Huang et al 2007;Kadri et al 2017).…”
Section: Brain Circuitry Engaged By Nmesmentioning
confidence: 99%
“…All the studies carried out on the basis of balance training (in various postural conditions: static, dynamic, unstable, progressive postural difficulty, with or without sensory manipulation) show that ipsilateral and/or contralateral monopedal postural control was improved after periods of 3-5 sessions weekly for 4-8 weeks (Rasool and George, 2007;Oliveira et al, 2013;Hale et al, 2014;El-Gohary et al, 2016;Schlenstedt et al, 2017). By contrast, the effects of resistance training of the ipsilateral limb on the contralateral monopedal postural control are much less clear since Kim et al (2011) reported that contralateral monopedal postural control was improved after 4 sessions weekly for 2 weeks while Kadri et al (2017) concluded that contralateral monopedal postural control was not improved after 3 sessions weekly for 8 weeks with either voluntary contractions or electro-induced contractions.…”
Section: Cross-education and Postural Control: Effects Of Training Avmentioning
confidence: 99%
“…Improvement in monopedal postural control of the contralateral limb after balance training can be ascribed to neural adaptations (Rasool and George, 2007;Oliveira et al, 2013;Hale et al, 2014;El-Gohary et al, 2016;Schlenstedt et al, 2017). The studies that have evaluated the effects of resistance training are not as clear and unanimous (Kim et al, 2011;Kadri et al, 2017). Balance training being specific to the evaluation task, whereas resistance training is not, it would be logical to assume that possible adaptations would not have the same origins.…”
Section: Mechanistic Explanations Suggestedmentioning
confidence: 99%
See 2 more Smart Citations